HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KECEMASAN PADA ANAK PENDERITA KANKER YANG MENJALANI KEMOTERAPI DI IRNA 4 RSUD dr. SAIFUL ANWAR MALANG: Relationship between Family Supportiand Anxiety Levels in Children with Cancer Undergoing Chemotherapy at IRNA 4 RSUD dr.iSaiful Anwar Malang - Tomy Hermono; Lilla Maria; Tanti Budhi Hariyanti (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2022)
Background : Cancer in children is one of the leading causes of death. Handling cancer in children will go through a series of chemotherapy treatment processes. In the preliminary study at RSUD dr. Saiful Anwar, approximately 80% of pediatric patients undergoing chemotherapy programs, mostly experience the psychological impact of anxiety. Objective : The design of this study is an observational analytic method with a cross sectional approach which aims to analyze the relationship between the relationship between family support and anxiety levels in children undergoing chemotherapy. Metodes: The sampling technique used purposive sampling on the parent population of cancer patients. The research instrument is a support questionnaire and an anxiety questionnaire (Zung Self Anxiety Rating Scale). Results : The results of the study obtained high family support as many as 56 respondents (83.6%), and the results showed that most patients with mild anxiety levels were 61 respondents (91%). Based on Spearman's statistical test, the r value of 0.356 (p value <0.05) showed that there was a weak relationship between family support and anxiety levels in cancer children undergoing chemotherapy. Therefore, families must be involved in mentoring during chemotherapy treatment in the hope of being able to have a positive impact during treatment.